ANALYSIS OF INTERNAL CONTROL STRATEGIES IN PREVENTING ACCOUNTING FRAUD IN MEDIUM SIZED MANUFACTURING COMPANY - Ibrohim, Ibrohim; Surachman, Surachman; Nurasiah, Iis (Yayasan Education and Social Center, 2025)
This study aims to analyze internal control strategies in an effort to prevent accounting fraud in medium-scale manufacturing companies in Banten Province. Accounting fraud is a serious problem that can harm the company and reduce stakeholder trust. The method used is qualitative with data collection through in-depth interviews, observations, and documentation in a number of manufacturing companies in the region. The results of the study indicate that the implementation of internal control in the company is still not optimal. The aspects of the control environment and management commitment are quite strong, but control activities such as segregation of duties and transaction authorization have not been implemented consistently. The financial information system is still manual, increasing the risk of data manipulation. In addition, internal audits experience limitations in terms of resources and independence, so that supervision is less effective. Fraud prevention strategies such as anti-fraud policies and whistleblowing reporting systems have also not been implemented evenly and are not supported by a transparent organizational culture. Therefore, companies need to strengthen internal control through digitalization of information systems, strengthening internal audits, and developing an anti-fraud culture so that the risk of accounting fraud can be minimized. This study contributes to the development of more effective internal control strategies, especially in medium-scale manufacturing companies in Indonesia.